From Petri Dish to Patient: Bioavailability Estimation and Mechanism of Action for Antimicrobial and Immunomodulatory Natural Products - Sadgrove, Nicholas John; Jones, Graham Lloyd (Frontiers in Microbiology, 2019)
The new era of multidrug resistance of pathogens against frontline antibiotics has compromised the immense therapeutic gains of the ‘golden age’, stimulating a resurgence in antimicrobial research focussed on antimicrobial and immunomodulatory components of botanical, fungal or microbial origin. While much valuable information has been amassed on the potency of crude extracts and, indeed, purified compounds there are too many reports that uncritically extrapolate observed in vitro activity to presumed ingestive and/or topical therapeutic value, particularly in the discipline of ethnopharmacology. Thus, natural product researchers would benefit from a basic pharmacokinetic and pharmacodynamic understanding. Furthermore, therapeutic success of complex mixtures or single components derived therefrom is not always proportionate to their MIC values, since immunomodulation can be the dominant mechanism of action. Researchers often fail to acknowledge this, particularly when ‘null’ activity is observed. In this review we introduce the most up to date theories of oral and topical bioavailability including the metabolic processes affecting xenobiotic biotransformation before and after drugs reach the site of their action in the body. We briefly examine the common methodologies employed in antimicrobial, immunomodulatory and pharmacokinetic research. Importantly, we emphasise the contribution of synergies and/or antagonisms in complex mixtures as they affect absorptive processes in the body and sometimes potentiate activity. Strictly in the context of natural product research, it is important to acknowledge the potential for chemotypic variation within important medicinal plants. Furthermore, polar head space and rotatable bonds give a priori indications of the likelihood of bioavailability of active metabolites. Considering this and other relatively simple chemical insights, we hope to provide the basis for a more rigorous scientific assessment, enabling researchers to predict the likelihood that observed in vitro anti-infective activity will translate to in vivo outcomes in a therapeutic context. We give worked examples of tentative pharmacokinetic assessment of some well-known medicinal plants.